Development of a Low-Cost Polymethylmethacrylate Stand-Alone Cervical Cage: Technical Note - Brenke, Christopher; Pott, Peter; Schwarz, Markus L.; Schmieder, Kirsten; Barth, Martin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background and Study Aims Stand-alone cervical cages aim to provide primary stability, yield solid fusion in the long-term course, and maintain physiologic alignment. However, many implants designed for these purposes fail in achieving these goals. Following implantation, relatively high rates of cage subsidence and failure of disc height maintenance may lead to cervical kyphosis and poor alignment of the cervical spine. At the same time, costs for cage implantation are relatively high compared with their unfavorable radiologic performance. Thus the aim of the study was to develop and test mechanically a low-cost polymethylmethacrylate (PMMA) cage with similar mechanical and procedural properties compared with a commercial polyetheretherketone (PEEK) cage.Material and Methods Following determination of the cage design, a casting mold was developed for the production of PMMA cages. Nine cages were produced and compared with nine PEEK cages using static compression tests for 0 and 45 degrees according to the recommendations of the American Society for Testing and Materials. Mean compressive yield strength, mean yield displacement, mean tensile strength, and mean stiffness were determined.Results At 0 degrees axial compression, the mean compressive yield strength, mean displacement, and mean tensile strength of the PMMA cage was significantly higher compared with the PEEK cage (p < 0.001). Stiffness of both implants did not differ significantly (p = 0.903). At 45 degrees axial compression, PEEK cages could not be investigated because slipping of the holding fixture occurred. Under these conditions, PMMA cages showed a mean compressive yield strength of 804.9 ± 60.5 N, a mean displacement of 0.66 mm ± 0.05 mm, a mean tensile strength of 7.92 ± 0.6 N/mm2, and a mean stiffness of 1,228 ± 79.4 N/mm.Conclusions The newly developed PMMA cage seems to show similar to superior mechanical properties compared with the commercial PEEK cage. Considering a preparation time of only 10 minutes and the low price for the PMMA material, the cost-benefit ratio clearly points to the use of the PMMA cage. However, clinical effectiveness has to be proven in a separate study.
Keywords: cervical spine; PMMA; ACDF; cervical cage